Enhancing the students problem-solving ability through situation-based learning with the six thinking hats technique - Suriwan Wongsa; Kanyarat Cojorn (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: Problem-solving ability is essential in learning, particularly in addressing complex situations that require multi-perspective analysis. Many students face difficulties in systematic thinking, leading to ineffective problem-solving. Enhancing this skill is crucial for overcoming daily challenges.Aims: This research aims to improve the problem-solving ability of Grade 11 students in Electrochemistry, targeting a minimum criterion of 70 percent proficiency, through the integration of Situation-Based Learning and the Six Thinking Hats technique.Methods: Employing action research, this study was conducted in three cycles with 31 Grade 11 students from Sarakhampittayakhom School, Thailand. Research instruments included: (1) lesson plans based on Situation-Based Learning and the Six Thinking Hats technique, (2) problem-solving ability tests, (3) observation sheets for problem-solving behaviors, and (4) student interview guides. Quantitative data were analyzed using averages and percentages, while qualitative data were evaluated through content analysis.Results: The findings indicate a significant improvement in students' problem-solving ability over the three cycles. In the first cycle, 13 students achieved the 70 percent  criterion, increasing to 20 students in the second cycle, and 28 students in the third cycle. This progression highlights the effectiveness of the proposed technique in enhancing problem-solving skills by fostering independent thinking, exploring diverse perspectives, and evaluating solutions comprehensively.Conclusion: Students receiving Situation-Based learning with the Six Thinking Hats technique show increased problem-solving ability. Therefore, this approach can significantly enhance the problem-solving ability of the target group.